2006
DOI: 10.1007/s11136-006-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between a functional independence measure (WeeFIM) and the pediatric quality of life inventory (PedsQL4.0) in young children with physical disabilities

Abstract: The WeeFIM and the PedsQL4.0 appear to assess related but different constructs, supporting the need to incorporate complementary measures when measuring general health of children with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
5
14
0
5
Order By: Relevance
“…Our findings are consistent with Grilli et al 8) who reported that the WeeFIM was not designed to measure a child's psychosocial integration and well-being. Higher cognitive skills do not necessarily lead to psychosocial wellbeing with other children.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with Grilli et al 8) who reported that the WeeFIM was not designed to measure a child's psychosocial integration and well-being. Higher cognitive skills do not necessarily lead to psychosocial wellbeing with other children.…”
Section: Discussionsupporting
confidence: 92%
“…The WeeFIM scores within our study sample indicate that children classified as the GMFCS II, IV, and V had more difficulties with ambulation than with the other subscales of the WeeFIM. However, Grilli et al 8) reported that self-care tasks and social cognition ability were lower than transfer and ambulation. These results are not in accordance with our findings because their sample had different characteristics from those of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neste sentido, Jankovich et al (2008), ressalta a importância do brincar no desenvolvimento infantil e defende o papel do terapeuta como facilitador do brincar, e Cusick, Lannin e Lowe (2007) certifica a possibilidade do uso da COPM adaptada à criança para avaliar a desempenho ocupacional nas áreas de auto-cuidado, produtividade e atividades de lazer. Grilli et al (2006) já utiliza um instrumento muldimensional para avaliação global em pediatria, baseado na Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF). Russell et al (1994) fala da complexidade de elaboração de um teste e do pouco uso que se faz da maioria deles depois de validado.…”
Section: A Importância Dos Relatos Dos Pais Como Método Avaliativounclassified